Dynamics of the Formation of the Nitrogen-Vacancy Center in Diamond (Communications in Computational Physics, 2018)
We present results of simulations of the energetics and dynamics involvedin the realization of the NV (nitrogen-vacancy) center in diamond. We use the self-consistentcharge-density functional tight-binding approximation and show that whenthe nitrogen resides on a single substitutional site, it fails to attract a vacancy, hence noNV center can be formed. However, if it occupies a split interstitial site and two vacanciesreside on the second or third neighbor sites, an NV center will form followingannealing at temperatures as low as $300℃$ and $650℃$, respectively. These results provideguidelines to experimentalists on how to increase the efficiency of NV formationin diamond.